Advancing disability inclusion through social and digital entrepreneurship in ASEAN - Widagdo, Ari Kuncara; Rahmawati, Rahmawati; Purnomo, Rochmat Aldy; Jaafar, Noor Ismawati; Markhumah, Umatun (International Journal of Innovative Research and Scientific Studies, 2025)
Based on explorative case studies from Indonesia and Malaysia, this study examines how inclusive social entrepreneurship can capture the transformative potential required to economically and socially empower persons with disabilities in Southeast Asia. This research study explores Identity Theory and Social Role Valorization (SRV) concepts from theoretical perspectives to understand the relevance and significance of identity formation, co-creation, and digital entrepreneurship in developing a sustainable model for empowerment. This study utilized a qualitative case study methodology through in-depth, semi-structured interviews with individuals and stakeholders, field observations, and thematic analysis, on the two enterprises Rumah Harapan Mulya (RHM) in Karangpatihan, Indonesia, and GOLD (Generating Opportunities for Learning Disabled) in Malaysia. This research shows that both programs work to integrate people with intellectual and developmental disabilities into their communities by providing adaptive vocational training, defining meaningful social roles, and creating multi-stakeholder partnerships. Despite their different approaches, RHM by traditional batik production and GOLD by culinary micro-enterprises both facilitate identity transformation and social inclusion. However, digital illiteracy, heavy reliance on volunteers, and poor infrastructure remain barriers to scaling digital entrepreneurship. The study emphasizes the need for systemic support, inclusive policy frameworks, and local adaptation to sustain the change in the long term. Finally, the research concluded that inclusive social entrepreneurship is both a viable and resilient development model for promoting disability inclusion and economic participation in ASEAN nations.